Lessons in perception : the Avant-Garde filmmaker as practical psychologist - Taberham, Paul (Berghahn, 2018)
Narrative comprehension, memory, motion, depth perception, synesthesia, hallucination and dreaming have long been objects of fascination for cognitive psychologists. They have also been among the most potent sources of creative inspiration for experimental filmmakers. Lessons in Perception melds film theory and cognitive science in a stimulating investigation of the work of iconic experimental artists such as Stan Brakhage, Robert Breer, Maya Deren, and Jordan Belson. In illustrating how avant-garde filmmakers draw from their own mental and perceptual capacities, author Paul Taberham offers a compelling for how their works expand the range of aesthetic sensitivity and open creative vistas uncharted by commercial cinema.